High-dimensional coherent one-way quantum key distribution - Sulimany, Kfir; Pelc, Guy; Dudkiewicz, Rom; Korenblit, Simcha; Eisenberg, Hagai S.; Bromberg, Yaron; Ben-Or, Michael (npj Quantum Inf, 2025)
High-dimensional quantum key distribution (QKD) offers secure communication with key rates that surpass those of QKD protocols utilizing two-dimensional encoding. However, existing high-dimensional QKD protocols require additional experimental resources, such as multiport interferometers and multiple detectors, thereby increasing the cost of high-dimensional systems and limiting their use. We introduce and analyze a high-dimensional QKD protocol that requires only standard two-dimensional hardware. We provide security analysis against individual and coherent attacks, establishing upper and lower bounds on the secure key rates. We tested our protocol on a standard two-dimensional QKD system over a 40 km fiber link, achieving a twofold increase in secure key rate compared to the standard two-dimensional coherent one-way protocol, without any hardware modifications. This work offers a significant improvement in the performance of already deployed QKD systems through simple software updates and holds broad applicability across various QKD schemes, making high-dimensional QKD practical for widespread use.
Publisher: Nature Publishing Group
Keywords: Fibre optics and optical communications; Information theory and computation; Photonic devices; quantum information